1988
DOI: 10.1136/ard.47.10.849
|View full text |Cite
|
Sign up to set email alerts
|

Immune mediated mechanism for thrombosis: antiphospholipid antibody binding to platelet membranes.

Abstract: SUMMARY Because thrombocytopenia occurs frequently in patients with anticardiolipin (aCL) antibodies and thrombosis, some investigators have proposed that aCL antibodies may play a direct part in thrombosis by binding and activating platelets. To test this proposal experiments were performed to determine whether aCL antibodies can bind platelets. Preincubation of aCL positive sera with freeze-thawed platelets caused significant inhibition of aCL activity in four serum samples tested. Antibodies with cardiolipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(103 citation statements)
references
References 21 publications
3
98
0
2
Order By: Relevance
“…The exact thrombogenic mechanisms of CAPSremain unclear. Several hypotheses previously implicated direct endothelial damage, platelet activation, inhibition of endogenous anticoagulation factors such as the complexthrombomodulin, protein C, protein S, antithrombin III, prekallikrein, and prostacyclin (8,9). Recently, the pathogenesis of CAPShas been reviewed in somedetail, and the role of activated vascular endothelium has been emphasized as an important factor (10).…”
Section: Discussionmentioning
confidence: 99%
“…The exact thrombogenic mechanisms of CAPSremain unclear. Several hypotheses previously implicated direct endothelial damage, platelet activation, inhibition of endogenous anticoagulation factors such as the complexthrombomodulin, protein C, protein S, antithrombin III, prekallikrein, and prostacyclin (8,9). Recently, the pathogenesis of CAPShas been reviewed in somedetail, and the role of activated vascular endothelium has been emphasized as an important factor (10).…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in ACLA levels was greater in patients having had an acute myocardial infarction than those who had not [88,89]. Another study revealed that more than 20% of young ( < 45 years of age) survivors of acute myocardial infarction harbored ACLAs; in those surviving, 61% having these antibodies experienced a later thromboembolic event [90]. No association was found between the presence of ACLAs and antinuclear antibody or other clinical features that would have suggested the presence of systemic lupus erythematosus.…”
Section: Anticardiolipins and Cardiac Diseasementioning
confidence: 94%
“…No association was found between the presence of ACLAs and antinuclear antibody or other clinical features that would have suggested the presence of systemic lupus erythematosus. Anticardiolipin antibodies are suggested as an indicator of increased risk for postmyocardial infarction thrombotic events and an indication for prophylactic anticoagulation or antiplatelet therapy [90]. Despite continuous prophylactic treatment with aspirin and warfarin, acute myocardial infarction has been documented in a patient with previously documented normal coronary arteries treated successfully with tissue plasminogen activator [91].…”
Section: Anticardiolipins and Cardiac Diseasementioning
confidence: 99%
“…Treatment of platelets with IgG aPL, or their F(ab) 2 fragments, in conjunction with subactivating doses of thrombin resulted in a significant increase in phosphorylation of p38 MAPK. Neither the IgG aPL nor their F(ab) 2 fragments increased significantly the phosphorylation of ERK-1/2 MAPKs.…”
mentioning
confidence: 99%
“…IgG fractions and their F(ab) 2 fragments were purified from the sera of 7 patients with APS and from the pooled sera of 10 healthy subjects (as controls). Phosphorylation of p38 MAPK, ERK-1/2, and [Ca 2؉ ]-dependent cytosolic phospholipase A 2 (cPLA 2 ) was determined in lysates of washed platelets pretreated with low doses of thrombin and aPL or control IgG or their F(ab) 2 fragments, by immunoblot. The effects of aPL on platelet aggregation in the presence or absence of a p38 MAPK inhibitor, SB203580, were examined.…”
mentioning
confidence: 99%